The Effect of Good Corporate Governance (GCG), Auditor Independence, and Audit Quality on the Integrity of Financial Statements (A Study on Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) for 2020–2023) - Aisyah Nabila; Wulandari, Putu Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The case of financial statement manipulation in the manufacturing industry demonstrates the importance of implementing Good Corporate Governance (GCG), auditor independence, and audit quality to maintain the integrity of financial statements. This study aims to analyze the influence of these three factors on manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The results of multiple linear regression analysis indicate that GCG significantly influences financial statement integrity, while auditor independence and audit quality do not have a significant partial effect. However, simultaneously, all three factors have a significant effect with an explanatory contribution of 50.1%. This finding emphasizes the importance of consistent GCG implementation supported by independent auditors and quality audits to strengthen transparency and investor confidence.